Immobilization, Characterization and Application of a Xylose Isomerase Biocatalyst for Xylose Fermentation in Biorefineries - Márcio D. N. Ramos; Juliana P. Sandri; Willian Kopp; Raquel L. C. Giordano; Thais S. Milessi (Fermentation)
A biocatalyst has been developed for application in the simultaneous isomerization and fermentation (SIF) of xylose, which could enable operation in repeated batches and the use of xylose from biomass hemicellulose for the production of second-generation (2G) ethanol. To this end, the enzyme xylose isomerase (XI) was immobilized on eleven different supports (based on chitosan, modified silica, agarose and magnetic supports) to obtain a derivative that is stable under process conditions and easy to recover from the fermented medium for future industrial application in biorefineries. Immobilization was performed with 5 mg/gsupport, with a support-to-suspension ratio of 1:20. Phosphate (pH 7.0) and carbonate–bicarbonate (pH 10.05) buffer were used for uni-point and multi-point immobilization, respectively. Among the immobilized enzymes, the magnetic microparticle Captura N exhibited the best immobilization parameters (67% recovered activity and half-life of 10 h at 80 °C), in addition to its magnetic properties, which facilitates purification. The SIF of crude sugarcane straw acid hydrolysate was carried out in repeated batches using XI-chitosan and XI-Captura N. Although economically promising, chitosan-based supports did not enhance enzyme stability. Therefore, magnetic microparticles are a promising option as XI immobilization supports for biorefinery applications.